JMV5656, A Novel Derivative of TLQP-21, Triggers the Activation of a Calcium-Dependent Potassium Outward Current in Microglial Cells - Rivolta, Ilaria; Binda, Anna; Molteni, Laura; Rizzi, Laura; Bresciani, Elena; Possenti, Roberta; Fehrentz, Jean-Alain; Verdié, Pascal; Martinez, Jean; Omeljaniuk, Robert J.; Locatelli, Vittorio; Torsello, Antonio (Frontiers in Cellular Neuroscience, 2017)
TLQP-21 (TLQPPASSRRRHFHHALPPAR) is a multifunctional peptide that is involved in the control of physiological functions, including feeding, reproduction, stress responsiveness, and general homeostasis. Despite the huge interest in TLQP-21 biological activity, very little is known about its intracellular mechanisms of action. In microglial cells, TLQP-21 stimulates increases of intracellular Ca2+ that may activate functions, including proliferation, migration, phagocytosis and production of inflammatory molecules. Our aim was to investigate whether JMV5656 (RRRHFHHALPPAR), a novel short analogue of TLQP-21, stimulates intracellular Ca2+ in the N9 microglia cells, and whether this Ca2+ elevation is coupled with the activation Ca2+-sensitive K+ channels. TLQP-21 and JMV5656 induced a sharp, dose-dependent increment in intracellular calcium. In 77% of cells, JMV5656 also caused an increase in the total outward currents, which was blunted by TEA (tetraethyl ammonium chloride), a non-selective blocker of voltage-dependent and Ca2+-activated potassium (K+) channels. Moreover, the effects of ion channel blockers charybdotoxin and iberiotoxin, suggested that multiple calcium-activated K+ channel types drove the outward current stimulated by JMV5656. Additionally, inhibition of JMV5656-stimulated outward currents by NS6180 (4-[[3-(trifluoromethyl)phenyl]methyl]-2H-1,4 benzothiazin-3(4H)-one) and TRAM-34 (triarylmethane-34), indicated that KCa3.1 channels are involved in this JMV5656 mechanisms of action. In summary, we demonstrate that, in N9 microglia cells, the interaction of JMV5656 with the TLQP-21 receptors induced an increase in intracellular Ca2+, and, following extracellular Ca2+ entry, the opening of KCa3.1 channels.